The Islamic State of Madinah was a Practical Manifestation of Justice, Equality, and Brotherhood - Dr. Peree Gul Tareen; Ms. Summaya Raza (Journal of Religion and Society, 2025)
The Islamic State of Madinah, established by the Prophet Muhammad (PBUH), serves as a timeless model of governance rooted in justice, equality, and brotherhood. This state laid the foundation for a pluralistic and inclusive society where individual rights and communal harmony were safeguarded through divine principles. Justice was upheld irrespective of race, religion, or social status, and economic fairness was ensured through systems like Zakat and prohibition of exploitation. Equality was not merely a concept but a lived reality, as seen in the treatment of citizens and minorities. Brotherhood transcended tribal boundaries, creating a unified community (Ummah) based on mutual respect and shared faith. This model continues to inspire modern governance systems that seek to balance moral values with administrative excellence. Keywords: Islamic State of Madinah, Justice, Equality, Brotherhood, Prophet Muhammad (PBUH), Governance, Ummah, Pluralism, Social Harmony